Preparation of ultrathin grafts for Descemet‐stripping endothelial keratoplasty with a single microkeratome pass. Issue 3 (January 2017) - Romano, Vito; Steger, Bernhard; Myneni, Jayavani; Batterbury, Mark; Willoughby, Colin E.; Kaye, Stephen B.
Abstract : N/A: We present a technique to achieve ultrathin Descemet‐stripping automated endothelial keratoplasty (DSAEK). Using a simple method of controlling artificial anterior chamber pressure and drying the corneal surface, it was possible to thin the donor cornea at a rate of 11 μm a minute. When the donor cornea was between 500 μm and 510 μm, a single pass was made using a 350 μm microkeratome head followed by a peripheral dissection. The resulting mean graft thickness was 83.2 μm ± 14.9 (SD) (range 50 to 98 μm) with a mean peripheral graft edge thickness of 106.8 ± 10.9 μm (range 90 to 120 μm). There were no surgical complications, and all grafts remained attached. This is a reliable method for preparing ultrathin donor corneal lenticules for DSAEK in the operating room or eye bank without using multiple microkeratome heads or risking double passes.